Enhancing design skills in art and design education - Oo, Tun Zaw; Kadyirov, Timur; Kadyjrova, Lyajsan; Józsa, Krisztián (Frontiers in Education, 2025)
IntroductionIn art and design education, design-based learning (DBL) is crucial for students’ design skills enhancement. Moreover, students’ motivation plays a significant role in their creative performance in design education. Therefore, this study aimed to explore the impact of students’ DBL and motivation on their design skills development in art and design education.MethodsNotably, 207 University students participated in the current experimental research. With the help of nonrandom sampling, the experimental group (102) and the control group (105) were divided. The experimental group was given the treatment with DBL and the control group with the traditional instructions.Results and discussionThe findings showed that experimental students who were treated by the DBL performed better in design skills assessment than those who were given traditional instructions. However, no gender difference was found in the analysis of covariance in the design skills assessment. Students’ motivation, such as intrinsic motivation, achievement motivation, and failure-avoidance motivation also have significant impacts on their design skills development. These research findings encouraged educators to be able to use the DBL technique in their design skills instructions.